Integrated Chemical-Biological Treatment of Benzo[a]pyrene - Zeng, Yu; Hong, P. K. Andrew; Wavrek, David A (Environmental science & technology, 2000)
Benzo[a]pyrene of natural and anthropogenic sources is one of the toxic, mutagenic, polycyclic aromatic hydrocarbons (PAHs) listed as priority pollutants. This study focuses on an integrated treatment of benzo[a]pyrene involving sequential chemical oxidation and biological degradation. The objectives are to (1) provide mechanistic details in the ozone-mediated degradation of benzo[a]pyrene in the aqueous phase, (2) test the biodegradability of resultant intermediates, and (3) test the feasibility for the coupled chemical-biological treatment of the five-ring PAH. Batch and packed column reactors were used to examine the degradation pathways of benzo[a]pyrene subject to ozonation in the aqueous phase. After different ozonation times, samples containing reaction intermediates and byproducts from both reactors were collected, identified for organic contents, and further biologically inoculated to determine their biodegradability. The O3-pretreated samples were incubated for 5, 10, 15, and 20 days; afterward biochemical oxygen demand (BOD), chemical oxygen demand (COD), and E. coli toxicity tests were conducted along with qualitative and quantitative determinations of benzo[a]pyrene, intermediates, and reaction products by GC/FID and GC/MS methods. Prevalent intermediates identified at different stages included ring-opened aldehydes, phthalic derivatives, and aliphatics. The degradation of benzo[a]pyrene is primarily initiated via O3-mediated ring-opening, followed by O3 and hydroxyl radical fragmentation, and ultimately brought to complete mineralization primarily via hydroxyl radicals. Intermediates formed during chemical oxidation were biodegradable with a measured first-order rate constant (k 0) of 0.18 day-1. The integrated chemical-biological system seems feasible for treating recalcitrant compounds, while pretreatment by chemical oxidation appears useful in promoting soluble intermediates from otherwise highly insoluble, biologically inaccessible benzo[a]pyrene.